Type of Performance Measurement System and Management Commitment - Fachruzzaman Fachruzzaman (Faculty of Economics and Business, Universitas Malikussaleh, 2021)
This study aims to categorize the performance measurement system and management commitment of Bengkulu regional apparatus, and obtain empirical evidence of the relationship between the performance measurement system and management commitment. This study uses a quantitative approach with a survey method. Primary data was collected using a questionnaire distributed to elements of leadership and staff involved in the planning, implementation and/or supervision process at the Regional Work Units (SKPD) in Bengkulu. The results show that the SKPD performance measurement system is categorized in the worst case with management commitment in the category of getting started but limited performance. Empirically, the performance measurement system has a relationship with management commitment.